The Role Of Rotavirus Immunization And Exclusive Breastfeeding In Supporting Gastrointestinal Tract Anatomy For The Prevention Of Childhood Diarrhea - Mira Mulya Dewi Cok Istri Agung; Alit Suka Astini Dewa Ayu Agung; Indah Kusumadewi Riandra Ni Putu (Poltekkes Kemenkes Semarang, 2026)
Diarrhea is a major public health problem causing morbidity and mortality in children under five years of age, particularly in developing countries like Indonesia. Low rates of exclusive breastfeeding and incomplete rotavirus immunization are important risk factors for diarrhea. This study aimed to examine the relationship between exclusive breastfeeding, rotavirus immunization status, and the incidence of diarrhea in children aged 6–24 months. The study used a case-control design with a quantitative approach, involving 80 respondents: 40 children with diarrhea and 40 children without diarrhea. Data were collected through structured questionnaires and medical record reviews and analyzed using the chi-square test. The results showed a significant association between exclusive breastfeeding and the incidence of diarrhea (p<0.05), with children who were not exclusively breastfed having a 4.18-fold higher risk of diarrhea (OR=4.188). Incomplete rotavirus immunization was also significantly associated with diarrhea, increasing the risk by 10.09 times compared to fully immunized children (OR=10.091). Exclusive breastfeeding and complete rotavirus immunization are significant protective factors against diarrhea in children at the primary healthcare level.